The Role of Human capital in Creating Sustainable Competitive Advantage for Culinary MSMEs in Madura Indonesia - Arifin, Miftahol; Purwanto, Edy; Hafidhah (Ilomata International Journal of Management, 2025)
MSMEs in the culinary sector in Madura have great potential to contribute to the regional and national economy. However, the challenges faced by culinary MSMEs in Madura are very diverse, including increasingly fierce competition, lack of skills, and limited access to training. In this context, it is important to understand the role of human capital in creating sustainable competitive advantages for Madurese culinary SMEs. This research aims to determine and analyze the role of human capital in creating sustainable competitive advantage in the Madurese culinary SME sector. The number of respondents in this study was 254 respondents who were selected using purposive sampling techniques. This research uses a quantitative approach, with data collection techniques using surveys (distributing questionnaires). Data analysis was carried out using the partial least square (PLS)-SEM application. A quantitative approach is used to identify the influence of human capital on sustainable competitive advantage. This research finds that human capital has a positive and significant influence on sustainable competitive advantage. Thus, it is hoped that this research can provide valuable insight for culinary MSME entrepreneurs in Madura in increasing their competitive advantage through developing human capital. In addition, this study is expected to provide understanding to academics and practitioners about the role of human capital in creating sustainable competitive advantage.